Can They Do It All? : Fiscal Space in Low-Income Countries - Baum, Anja (IMF Working Papers; Working Paper ;, 2017)
According to U.N. estimates, low-income countries will have to increase their annual public spending by up to 30 percent of GDP to achieve the Sustainable Development Goals (SDGs), raising the question of whether they can do it all. This paper develops a new metric of fiscal space in low-income countries that accounts for macroeconomic uncertainty, allowing us to assess whether those spending needs can be accommodated. Illustrative simulations based on this methodology imply that, even under benign conditions, the fiscal space available in lowincome countries is likely insufficient to undertake the spending needed to achieve the SDGs. Improving public investment efficiency and domestic revenue mobilization can somewhat narrow the gap but it will require major efforts relative to recent trends.